'Something That Unites Us All': Understandings of St. Patrick's Day Parades as Representing the Irish National Group. (6th May 2015) - O'Donnell, Aisling T.; Muldoon, Orla T.; Blaylock, Danielle L.; Stevenson, Clifford; Bryan, Dominic; Reicher, Stephen D.; Pehrson, Samuel
Abstract: The present study investigates how attendees at national celebratory crowd events—specifically St. Patrick's Day parades—understand the role of such events in representing and uniting the national community. We conducted semi‐structured interviews with people who attended St. Patrick's Day parades in either Dublin or Belfast. In year 1, full‐length interviews were conducted before and after the events ( N = 17), and in years 1 and 2, shorter interviews were conducted during the events (year 1 N = 170; year 2 N = 142). Interview data were analysed using thematic analysis, allowing the identification of three broad themes. Participants reported that (i) the events extend the boundary of the national group, using participation to define who counts as Irish; (ii) the events strategically represent the nature of the national group, maximising positive images and managing stereotypical representations; and (iii) symbolism serves to unify the group but can also disrupt already fragile unity and so must be managed. Overall, this points to a strategic identity dimension to these crowd events. We discuss the implications of these findings for future research in terms of the role of large‐scale celebratory events in the strategic representation of everyday social identities. © 2015 The Authors. Journal of Community & Applied Social Psychology published by John Wiley & Sons Ltd.